Optimal economic productivity of exopolysaccharides from lactic acid bacteria with production possibility curves. Issue 7 (3rd June 2019) - Lin, Tachen; Chen, Chunyeh; Chen, Bangyuan; Shaw, Jeifu; Chen, Yuhshuen
Abstract: It is important that exopolysaccharides (EPS) of lactic acid bacteria (LAB) with antioxidant activities are produced economically, as it can confer beneficial effects on human health. A model of production possibility curve (PPC) was conducted to the optimal productivity of EPS for the purpose of economic production. The results revealed that the optimal productivity of EPS was approached to the set by NB (90%) and MRS (55%) broth from PPC with equation of PPC(Y) = 100–0.0335*EXP(0.08*X). The EPS productivity and yield of strain LaP with optimal production set (OPS) were, respectively, 291.0 ± 2.6 mg and 13.5 ± 0.7%, and the cost of OPS can be saved by about 31.6%, while that for strain BaP were 280.7 ± 2.5 mg and 13.0 ± 0.7%, respectively, and with 31.6% saved as well. Besides, the EPS produced from PPC mode has appropriate antioxidant ability with 34.6 ± 0.7% (LaP) and 37.6 ± 0.9 (%) (BaP) of DPPH radical scavenging activity under the economic cost. The strategy of controlling the medium composition not only could improve the productivity of EPS, but also enhance the antioxidant effects of EPS. Both LaP and BaP with antioxidant potential may be useful as supplements in the health‐promoting food industry. Abstract : Develop innovatively a model of production possibility curve (PPC) of the optimal production method by biotechnology based on economic theory of Pareto optimality theory. Not only promote production and reduce costs, but also strengthen the antioxidant functions of exopolysaccharides (EPS). EPS was conductive to be useful as food supplements and could have more potential application to the healthy food industry.